Teachers' Perspectives on ICT Curriculum and Students' Learning Skills - Hanene Lahiani; Hani Y. Aljarrah; Hatem Alqudah; Suad A. Alwaely (Emerging Science Journal, 2023)
Objectives: The role of technology in modern life is expanding rapidly. Educational technology has emerged as a crucial component in raising academic achievement worldwide. Teachers all over the world are now focusing on it. Therefore, this study examined the teachers' perspectives on the ICT curriculum and its effect on students' eLearning skills in the UAE. Methods/Analysis: Researchers used a questionnaire to gather the data to learn more about how technology is being used in UAE Model Schools. There were a total of 150 teachers (60 female and 90 male) from three different Abu Dhabi schools included in the study. In addition, the study used descriptive statistics for the analysis. Findings: The study's findings confirmed that teachers at both institutions use technology in the classroom. Novelty /Improvement:Practical implications for the United Arab Emirates support of technology are explored. Doi: 10.28991/ESJ-2023-SIED2-03 Full Text: PDF